Sejarah Kerajaan Fatuleu Pada Masa Pemerintahan Raja Kooi Thaiboko Tahun 1913-1930 - Missa, Rini B.; Djakariah, Djakariah; Utomo, Susilo Setyo (FLORESIENSIS, 2023)
This study aims to reveal (1) the history of the establishment of the Fatuleu Kingdom in 1913, (2) the political, economic and social conditions of the Fatuleu Kingdom during the reign of King Kooi Thaiboko from 1913 to 1930. The research method used ihistorical research employing heuristic steps, historical criticism, interpretation, and historiography. The research findings indicate that (1) the history of the establishment of the Fatuleu in 1913 began with the Bipolo War and the defeat of King Sonbai by the Dutch. (2) The political structure of the Fatuleu Kingdom consisted of the following: the King (usif), Fetor (ate), Temukung, and the Community (to). The economic sector of the Fatuleu Kingdom community was very prosperous because it had abundant agricultural and livestock products, coupled with King Kooi Thaiboko's policy to build roads, bridges and open fields to improve the economy of his people.